Velocity analysis of a six wheel modular mobile robot using MATLAB-Simulink. Issue 1 (March 2021) - Fernando, A; GanLim, L
Abstract: This paper presents the modelling and simulation of a six wheeled three body modular robot in MATLAB Simulink. The modules are modelled as an independent differential drive wheeled mobile robot. Velocity and distance were measured using three different configurations: two wheel, four wheel and six wheel configuration. The simulation result was able to predict the response of the modular body in different configurations in terms of velocity and distance with contact forces acting upon it.